Global Perspectives on China's Belt and Road Initiative Asserting Agency through Regional Connectivity - Schneider, Florian (Amsterdam University Press, 2021)
2013 saw the launch of the largest, most influential investment initiative in recent memory: China's Belt and Road Initiative (BRI). This globe-spanning strategy has reshaped local economies and regionals networks, and it has become a contested subject for scholars and practitioners alike. How should we make sense of the complex interactions that the BRI has enabled? Understanding these processes requires truly global perspectives alongside careful attention to the role that local actors play in giving shape to individual BRI projects. The contributions in this volume provide both 'big picture' assessments of China's role in regional and global interactions and detailed case studies that home in on the role agency plays in BRI dynamics. Written by leading area studies scholars with diverse disciplinary expertise, this book reveals how Chinese efforts to recalibrate the world are taken up, challenged, revamped, and reworked in diverse contexts around the world.